Investigation of the Blockchain’s Influence on Traditional Banking: Challenges and Opportunities - Pakenaite, Simona; Taujanskaite, Kamile (European Scientific Journal, ESJ, 2019)
New technologies is constantly becoming more and more important for our dynamically changing society, and it occupy greater importance of nowadays’ financial sector. This paper focuses on the investigation of the Blockchain and its impact on traditional banking in a qualitative way. The theoretical part of the research presents general overview, brief technical operating principles, main risks, and opportunities of the decentralized networking. The second part examines key properties, main limitations, pros and cons of the Blockchain as well as wider applicability in the financial sector based on experts’ evaluation. The results of the expert evaluation provides core records about bank weaknesses and key aspects of the Blockchain influence for financial sector in conformity with 32 professionals. Findings of the research are very relevant while technologies are emerging enormously. Bank collaboration (and not the competition) with fintech is indispensable since both have strengths and weaknesses. However, new technologies, especially peer-to-peer computing, continually gains attention (positive or negative) from the researchers, media, and public. Methods used in the research are: scientific literature analysis, statistical data analysis, comparative analysis, and expert evaluation.